ASSESSMENT OF TIME MANAGEMENT SKILLS AMONG STAFF NURSES - SHAUKAT, S; SADDIQUE, H; TASNEEM, SS (Biological and Clinical Sciences Research Journal, 2024)
Time management is an essential skill in the nursing profession, directly impacting individual performance, patient care quality, and the overall efficiency of healthcare organizations. Despite its importance, many nurses struggle with effective time management, leading to increased stress and reduced job satisfaction. Objective: This study aims to assess the time management skills of staff nurses in tertiary care hospitals and identify areas for improvement. Methods: A descriptive cross-sectional study was conducted in selected wards of tertiary care hospitals. A total of 142 staff nurses participated in the study. Data were collected using a structured questionnaire, which included 22 Nurse’s Time Management Inventory items. Responses were scored on a 3-point Likert scale, and nurses were classified into low, moderate, and high time management categories. Statistical analysis was performed using SPSS software (version 25), with descriptive statistics used to summarize the data. Results: The study found that 64.8% of the nurses demonstrated moderate time management skills, while 31.0% had low time management abilities. Only 4.2% of the participants exhibited high time management skills. Most nurses were in the 31-35 age group, predominantly female, and had 6-10 years of work experience. The study highlighted a significant need for improvement in time management skills among the nursing workforce. Conclusion: The findings indicate that while most nurses possess moderate time management skills, a substantial portion struggle with effectively managing their time. These results underscore the necessity for targeted interventions, including structured training programs, to enhance time management abilities among nurses, thereby improving both job performance and patient care outcomes.